Are Routine Dilatations Necessary Post Pull-Through Surgery for Hirschsprung Disease? - Aworanti, Olugbenga; Hung, Judy; McDowell, Dermot; Martin, Ian; Quinn, Feargal (European Journal of Pediatric Surgery, 2013)
Introduction We aim to compare the anastomotic stricture and enterocolitis rates between groups who either had or did not have anal dilatations (AD or NAD) prescribed routinely post pull-through surgery for Hirschsprung disease (HD); by this means, we will evaluate the benefit of routine dilatations.Methods A retrospective review of the records of all children operated on for HD between 1997 and 2010 was performed. Associated Down syndrome and total colonic aganglionosis were excluded. Two cohorts were identified; those who had anal dilatation prescribed routinely (AD) and those who did not (NAD). In the latter group, if an anastomotic stricture was subsequently diagnosed, anal dilatations were initiated. The anastomotic stricture and enterocolitis rates between groups were compared. Significance was set at p < 0.05.Results There were 73 children that met the inclusion criteria (30 AD and 43 NAD). The NAD group had the longer mean follow-up period of 91 versus 59 months (p = 0.026); however, follow-up duration was unrelated to the anastomotic stricture rates (p = 0.575) and enterocolitis rates (p = 0.150). The anastomotic stricture rates were 13% (n = 4) versus 14% (n = 6) (p = 1.000) for the AD and NAD groups, respectively (relative risk [95% confidence interval] RR [95% CI], 0.95 [0.29 to 3.09]; p = 0.94). The mean duration between surgery and stricture occurrence was 348 versus 74 days for the AD and NAD groups, respectively. The enterocolitis rates were 23% (n = 7) versus 28% (n = 12) (p = 0.788) for the AD and NAD groups, respectively (RR [95% CI], 0.84 [0.37 to 1.87]; p = 0.66).Conclusion We have not shown a reduced risk of developing anastomotic strictures or enterocolitis if anal dilatations are prescribed routinely. However, when routine dilatations were prescribed, predominantly late onset strictures of perhaps a different etiology occurred.
Keywords: anal dilatations; anastomotic stricture; enterocolitis; Hirschsprung disease; anal stenosis